1967
DOI: 10.1002/anie.196704021
|View full text |Cite
|
Sign up to set email alerts
|

The Norcaradiene Problem

Abstract: Dedicated to Professor R. Criegee on the occasion of his 65th birthdayCompounds having the norcaradiene structure are stable if one of the double bonds of the norcaradiene also belongs to a benzene ring or if C atoms I and 6 are fixed in position by a bridge. A similar effect that favors the norcaradiene form is produced by the incorporation of nitrogen atoms in positions 3 and 4. Cycloheptatriene and most of the simply substituted tropilidenes exist exclusively in the monocyclic triene form. It has been possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
39
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(39 citation statements)
references
References 197 publications
0
39
0
Order By: Relevance
“…10 The synthetic utility of this transformation was greatly improved with the advent 4 catalyzes the reaction between ethyl diazoacetate (1) and benzene (13) at room temperature to quantitatively yield cycloheptatriene 3.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…10 The synthetic utility of this transformation was greatly improved with the advent 4 catalyzes the reaction between ethyl diazoacetate (1) and benzene (13) at room temperature to quantitatively yield cycloheptatriene 3.…”
mentioning
confidence: 99%
“…As will be discussed later, substrates with three-atom tethers are prone to cyclopentanone formation via C-H insertion. 18 In an early demonstration of the utility of the Rh-catalyzed intramolecular Buchner reaction, McKervey and Kennedy reported that exposure of a-diazo ketone 16 to catalytic Rh 2 (mandelate) 4 quantitatively provided a mixture of norcaradiene 17 and cycloheptatriene 18.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Cycloheptatrienylacetylene 2 is rather unreactive under the dimer-forming reaction conditions in the absence of DBU, and at elevated temperature it gave tricyclo [3.2.2.02'4] nona-6-ene or 6, 8-diene type adducts by the reactions with dienophiles.…”
mentioning
confidence: 99%
“…The position of the equilibrium between cycloheptatriene and norcaradiene can be changed by the judicious introduction of substituents (1). Particularly dramatic shifts in the equilibrium position have been observed with substitution at C,, the methylene carbon of these systems (2).…”
mentioning
confidence: 99%